Banking sector race to efficiency during corona crisis: Does size matter? - Josip Visković; Lana Kordić; Marko Miletić (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: The consolidation of the banking market in Croatia is characterized by a decreasing number of banks, especially small banks. The inability to remain in the market is often the result of the inability to maintain sustainable efficiency over time. Therefore, the main aim of the study was to determine whether small banks can successfully participate in the efficiency race with large banks. Furthermore, it was essential to clarify whether the efficiency gap arises from technical or scale efficiency. Finally, we also analyse how the COVID-19 pandemic crisis has affected efficiency and the difference between large, medium, and small banks. Design/methodology/approach: The efficiency development of the Croatian banking sector over eight years is examined using the Malmquist - DEA performance measure under the assumption of variable returns to scale (BCC model) and using the input-oriented DEA model. We use the intermediary approach for defining input and output variables, and the study covers the period from 2013 to 2020. Data are taken from ORBIS database. Findings: Banks in Croatia increased their total factor productivity by 2.2% on average, mainly due to an increase in technological change (1.93%), implying innovation and new banking services. Moreover, the COVID-19 pandemic crisis has further accelerated the race for efficiency. Indeed, the results show that the improvement in efficiency was more remarkable than the average of the period studied, especially in terms of technical efficiency (1% in 2020 compared to the mean of the period of 0.28%), but also due to technological efficiency (2.02% in 2020 compared to the mean of the period of 1.93%). Finally, the COVID-19 pandemic crisis affected efficiency in different ways with respect to the size of banks. Large banks improved their total factor productivity by 7.19%, small banks by 2.64%, and medium-sized banks reduced it by 1.38%. In addition, large banks achieved efficiency improvements due to technological change, while small banks focused on both technical (1.70%) and technological (0.98%) efficiency improvements. Research limitations/implications: One of the limitations of the paper was that during period some takeovers were conducted in Croatian banking sector and therefore some banks were omitted from sample. Additionally, ORBIS database does not cover some data that could be better as indicators of outputs. Therefore, future research on this topic could include other input-output variables such as assets/labor and revenue (income). Our results suggest that innovation in the delivery of banking services is critical to maintaining the race for efficiency. Therefore, our results may lead managers to focus on technological change in the long run, but especially in times of crisis. Managers of small banks should focus on both managerial and technological improvements. Originality/value: This study primarily makes an empirical contribution to the topic of efficiency in the banking sector. We have analysed the impact of the COVID -19 pandemic crisis on banking efficiency, with particular attention to the size effect, which, to our knowledge, has not yet been thoroughly studied. Future research could build on this study by taking into accountother input-output variables and sample of CEE countries.
Keywords: D24; G21; 330; Croatian banking sector; total factor productivity; size; COVID-19 pandemic crisis; Malmquist DEA index